Assessing Young Children’s Oral Language: Recommendations for Classroom Practice and Policy - Malec, Alesia; Peterson, Shelley; Elshereif, Heba (Canadian Journal of Education/Revue canadienne de l’éducation, 2017)
A systematic review of research on oral language assessments for four-to-eight-year- old children was undertaken to support a six-year action research project aimed toward co-creating classroom oral language assessment tools with teachers in northern rural and Indigenous Canadian communities. Through an extensive screening process, 10 studies were assessed as highly rated and identified for inclusion in the final review. Narrative, vocabulary, and syntax assessments were the most common assessment types found in the final review. Assessment practices in all studies in the final review involved gathering language samples in one-on-one adult-directed contexts. The systematic review also revealed that a preponderance of the research on young children’s oral language assessment has been published in speech-language pathology and language testing journals. Although educational researchers recognize the importance of oral language to children’s literacy and learning, there is a paucity of research on oral language assessment conducted by educational researchers and published in educational research journals. Implications to policy and classroom practice include recommendations for increased research collaboration between speech-language pathology researchers and literacy researchers along with input from early childhood educators to develop oral language assessment instruments that support children’s oral language in classroom settings.